Analysis of the attitudes of pre-service science teachers on renewable energy sources - Uğraş, Mustafa; Aksakal, Şeyma (Sakarya University, 2016)
The present study was conducted to determine the attitudes of pre-service science teachers on renewable energy sources. Mixed methodology was used to determine the attitudes of pre-service science teachers in depth in the study. Study sample included 116 freshmen, sophomore and junior students attending Fırat University Faculty of Education, Science Teaching Department. Renewable energy sources attitude scale developed by Güneş, Alat and Gözüm (2013) and which has a reliability coefficient of .87, and an interview form were used as data collection tools. Study findings demonstrated that pre-service teachers generally had a positive attitude towards renewable energy sources. It was determined that training on renewable energy sources was important since there would be projects in classes in their future careers. Pre-service teachers stated that utilizing renewable energy sources would contribute to national economies and their development and the environment would be protected. Pre-service teachers demonstrated that Turkey was not a developed country in renewable energy use due to the lack of adequate technological infrastructure and awareness among the people. © The Turkish Online Journal of Educational Technology.
Keywords: Attitude; Pre-service science teachers; Renewable energy sources; Socio-scientific subjects